Selection of a Hydroxypropylcellulose Grade for 3D-Printable Paroxetine Formulations by Fused Deposition Modelling - Sara Figueiredo; João F. Pinto; Fátima G. Carvalho; Ana I. Fernandes (Medical Sciences Forum, 2023)
This work presents the preliminary development of paroxetine-based formulations containing hydroxypropylcellulose (HPC) polymers suitable for hot-melt extrusion coupled to fused deposition modeling (3D printing). Two grades of HPC (54% w/w), KlucelTM LF and KlucelTM GF, were tested in a polymeric formulation of paroxetine (30% w/w) and adjuvants (16% w/w of dicalcium dihydrate phosphate, magnesium stearate, and triethylcitrate; 10:1:5 ratio). Both formulations exhibited a release of almost 100% of paroxetine after 12 h, but the drug released from the KlucelTM LF formulation was quicker and closer to the formulations available in the market.